Entrepreneurship and ESG Convergence: Improving Business Performance in Emerging Markets - Martinus Calvin Saputra; Christian Herdinata; Damelina Basauli Tambunan; David Sukardi Kodrat; Tommy Christian Efrata (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objectives: This study aims to examine the relationship between entrepreneurial orientation (EO), environmental, social and governance (ESG), and corporate business performance (CBP) in multinational companies operating in Indonesia.Methodology: The research method used is quantitative. This data was obtained from 50 managers who completed the survey through Google Forms. The collected data is analyzed using PLS to verify the relationships between variables.Findings: Results show that EO and ESG investments increase GST positively and significantly. In addition, ESG investments can also act as intermediaries that reinforce the positive effects of executive orders on GST.Conclusion: This study shows that multinational companies in developing countries increase profits while supporting sustainability goals. This can be achieved by aligning the company's innovation strategy with ESG principles. Businesses must not only have profits but also the ability to create sustainable long-term growth. In addition, the results of this study can also serve as practical guidance for business leaders and policymakers in encouraging sustainable development and strengthening entrepreneurship.